1988
DOI: 10.1002/aja.1001820206
|View full text |Cite
|
Sign up to set email alerts
|

Early development of the hypoglossal nerve in the chick embryo as observed by the whole‐mount nerve staining method

Abstract: The developmental morphology of the hypoglossal nerve and associated structures were studied in the chick embryo (Hamburger and Hamilton stages 16-27) stained by the immunohistochemical technique. Ventral rootlets of the occipital nerves, including O1, were seen at stage 16. The distal ends of these nerves anastomosed to form the hypoglossal nerve at stage 20. At stage 23, four occipital and the first three cervical nerves were observed to be involved. The transient contribution of C3 at this stage seemed to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 28 publications
4
50
0
1
Order By: Relevance
“…Prior studies suggested that such transient ganglia can occur normally in vertebrates (33); however, these abnormalities were observed more often in Sall3 Ϫ/Ϫ animals. In half of the affected mutant animals, these supernumerary ganglia were also bilateral, while in the control animals, these structures were always unilateral (data not shown).…”
Section: Sall3mentioning
confidence: 72%
“…Prior studies suggested that such transient ganglia can occur normally in vertebrates (33); however, these abnormalities were observed more often in Sall3 Ϫ/Ϫ animals. In half of the affected mutant animals, these supernumerary ganglia were also bilateral, while in the control animals, these structures were always unilateral (data not shown).…”
Section: Sall3mentioning
confidence: 72%
“…In addition, a number of large ganglia in the CNS now showed strong pask expression. Froriep's ganglion, which is a vestigial DRG whose components later break down to give rise to the motor neuron elements of the hypoglossal (XII) ganglion (Kuratani et al 1988), the vestibulocochlear (VIII) ganglion, and the glossopharyngeal (IX) ganglion, all expressed pstk1. There was also continued expression of pstk1 in the myocardium and dorsal root ganglia.…”
Section: Expression In the E15 Embryomentioning
confidence: 99%
“…The staining procedure was developed and verified in previous studies (Ishikawa et al, 1986;Kuratani et al, 1988aKuratani et al, , 1988b and used with some minor modifications as follows.…”
Section: Whole-mount Immunostainingmentioning
confidence: 99%
“…In this animal, symmetric large blood vessels, which have disappeared in most mammals during their evolutionary development, are preserved and optimal for providing clues about the arterial and venous portae, that is, the entrances to the heart of arteries and veins, because great vessels are considered to play a role as a guide for the peripheral sympathetic cardiac nerves from their origin to the heart. Whole-mount immunostaining is very useful to trace the three-dimensional structure of fine sympathetic cardiac nerves without making serial sections (Ishikawa et al, 1986;Kuratani et al, 1988aKuratani et al, , 1988b. Previously, Tanaka et al (1998) reported on the parasympathetic cardiac nerves in the house musk shrew, but no reports have been made on the sympathetic cardiac nerves in this species.…”
mentioning
confidence: 99%